Evaluation of cellular immune response in Golden Hamsters experimentally infected with Leishmania donovani comparing with cellular immune response against chicken Red Blood Cells. (Baghdad Science Journal, 2012)
The Evaluation of the immune response in Golden Hamsters experimentally infected with Leishmania donovani was determined in this study, particularly, the cellular immune response. Follow up has maintained to determine the Delayed Type of Hypersensitivity using skin test both in infected and control lab animals. Chicken red blood cells were used as a parameter to evaluate the immune system; they are dull and have the ability of immunization. Two concentrations of chicken R.B.C were examined to determine which gives the higher titration in Hamsters and those were 1.5 X 109 cell/ml and 3 X 109 cell/ml , the second concentration gave the maximum titration where then used in this work. After sensitization with Chicken R.B.C for both infected and control groups, delayed type of hypersensitivity has been used against Leishmania donovani antigen and 4 days of follow up were adopted and they were (14, 30, 60, 90) day after infection. Results showed that skin test against both antigens ( L.donovani and chicken R.B.C) was significantly higher than normal at the first day of follow up ( day 14) then gradual decreasing were noticed till the last day of follow up (90). This can indicate that the infection with L.donovani activated the immune response at the beginning of infection, then leads to cellular immune suppression against both L.donovani antigen and chicken R.B.C., so that this immunosuppression is not specific.